Functionalization of side chain terminals with fused aromatic rings in carbazole–diketopyrrolopyrrole based conjugated polymers for improved charge transport properties. Issue 100 (13th October 2016) - Sun, Ying; Huang, Qizan; Zhang, Xueqin; Ding, Xiaojing; Han, Pei; Lin, Baoping; Yang, Hong; Guo, Lingxiang
Abstract : Through functionalization of the side chain terminal with fused aromatic rings, the charge transport properties of carbazole–diketopyrrolopyrrole based polymers were improved. Abstract : In recent years, side chain engineering has been proven to play a critical role in the development of high performance conjugated polymers for organic electronics. Here, we report a new strategy to improve charge transport property through side chain functionalization. A series of carbazole–diketopyrrolopyrrole based conjugated polymersP1, P2 andP3 with different side chains have been designed and synthesized. ForP2 andP3, a pyrene and carbazole unit were incorporated into the terminal of the alkyl side chain, respectively. Thermal properties, crystallinities, UV-vis absorptions, electrochemical properties as well as charge transport properties of the polymers were investigated in detail. Interestingly, results showed that incorporation of the fused aromatic ring into the side chain terminal not only changed the absorption and electrochemical properties, but also affected the charge transport properties. The pyrene and carbazole group in the side chain terminal significantly promoted aggregation of the polymer chains, which would provide short-range order for improved charge carrier mobility. Compared to the hole mobility (0.019 cm 2 V −1 s −1 ) for polymerP1 with the whole alkyl chains, increased hole mobilities of 0.081 cm 2 V −1 s −1 and 0.052 cm 2 V −1 s −1 were achieved for polymerP2 and polymerP3, respectively. It is worthy to note that our strategy gives rise to no increment of the crystallinity of the polymer, being beneficial for the practical application of soft electronics since high crystallinity of the material usually leads to poor thin film uniformity and weak mechanical resilience. In this respect, we offer a promising tool to aid rational polymer design for enhanced charge transport property.